Impact of concomitant medications on obstructive sleep apnoea. (24th November 2016) - Jullian‐Desayes, Ingrid; Revol, Bruno; Chareyre, Elisa; Camus, Philippe; Villier, Céline; Borel, Jean‐Christian; Pepin, Jean‐Louis; Joyeux‐Faure, Marie
Abstract : Obstructive sleep apnoea (OSA) is characterized by repeated episodes of apnoea and hypopnoea during sleep. Little is known about the potential impact of therapy drugs on the underlying respiratory disorder. Any influence should be taken into account and appropriate action taken, including drug withdrawal if necessary. Here, we review drugs in terms of their possible impact on OSA; drugs which (1) may worsen OSA; (2) are unlikely to have an impact on OSA; (3) those for which data are scarce or contradictory; and (4) drugs with a potentially improving effect. The level of evidence is ranked according to three grades: A – randomized controlled trials (RCTs) with high statistical power; B – RCTs with lower power, non‐randomized comparative studies and observational studies; C – retrospective studies and case reports. Our review enabled us to propose clinical recommendations. Briefly, agents worsening OSA or inducing weight gain, that must be avoided, are clearly identified. Drugs such as 'Z drugs' and sodium oxybate should be used with caution as the literature contains conflicting results. Finally, larger trials are needed to clarify the potential positive impact of certain drugs on OSA. In the meantime, some, such as diuretics or other antihypertensive medications, are helpful in reducing OSA‐associated cardiovascular morbidity.